Enhanced topical delivery of tacrolimus by a carbomer hydrogel formulation with transcutol P. (2nd October 2016) - Lee, Sang Gon; Kang, Jong Bu; Kim, Sung Rae; Kim, Chae Jin; Yeom, Dong Woo; Yoon, Ho Yub; Kwak, Seong Shin; Choi, Young Wook
Abstract: Tacrolimus (TAC), a non-steroidal anti-inflammatory and immunosuppressive agent, is used for the treatment of atopic dermatitis (AD) and skin immune diseases. TAC-loaded topical hydrogel formulations composed of carbomer, carnosine, transcutol P (diethylene glycol monoethyl ether) and humectant were prepared. For comparison, TAC-loaded topical cream-type formulations were also prepared and commercially available TAC ointment was used as a reference. A drug release study in vitro revealed that the total amount of TAC released from hydrogels over 24 h was approximately 30 times greater than that for the reference formulation. Compared to the reference ointment and creams, carbomer gel formulations showed higher skin permeation and retention of TAC (significantly different at p < 0.05), especially those with more than 10% of transcutol P. Therefore, carbomer gel formulations with sufficient levels of transcutol P are good candidates for skin delivery of TAC and have potential as therapeutic agents for the treatment of AD or immune skin disorders.